Does One Size Fit All? The Consequences of Switching Markets with Different Regulatory Standards. - Jenkinson, T; Ramadorai, T (Oxford Finance, 2009)
As the regulation of public companies has progressively tightened in recent years, many companies have chosen to switch to stock exchanges with lower regulatory requirements. We analyse the consequences of switching for smaller quoted companies, using the unusual regulatory environment in London, which has two markets with different regulatory regimes but the same trading technology. Firms that switch to lighter regulation experience negative announcement returns of approximately 4%. However these initial price reactions are reversed after the actual switch. We also find an intriguing longer-term upward drift in stock returns, which we relate to improved operating performance.